Application of Layered Double Hydroxides as Host in Controlled Release Formulation of Latex Stimulant and Metal Catalyst in Formation of Carbon Nanotube - Mohamad Jaafar, Adila (2010)
Layered double hydroxides (LDH) have attracted a lot of attention in research area due to its unique properties. LDHs has proven to be useful in various fields of applications and due to that, LDHs have been chosen to be used in this study as precursor in two applications which are; as host in a latex stimulant controlled release formulation and metal catalyst in the formation of carbon nanotubes. Manipulation of LDHs could lead to the formation of various useful materials and this is contributed by the interesting property of LDHs which are ion exchange and high metal dispersion. From the study, the syntheses of latex stimulant nanocomposites, controlled release of latex stimulant in various aqueous solutions and formation of carbon nanotubes were proven to be successful. It is hoped that in the future the knowledge of LDHs could lead to application of many beneficial materials in various fields. In this study, Zinc-Aluminium-nitrate-LDH (ZAL) synthesised at different Zn/Al molar ratios, R=2-4 and pH = 7.50-10.00 were successfully synthesised via co-precipitation method under N2 atmosphere. Latex stimulant agent of 2,4-D and 2-CEPA have been successfully inserted into the lamella of layered double hydroxides via co-precipitation. Various parameters namely Zn to Al molar ratios of the mother liquor which are 2, 3 and 4; concentrations of anion, 2,4-D and 2-CEPA which are 0.08 M- 0.32 M; and pH which are 7.50 - 10.00 have been tested during the synthesis of Zn-Al-2,4-D (ZANDI) and Zn-Al-2-CEPA (ZANE) nanocomposites. X-ray diffraction patterns showed expansion of the precursor‟s basal spacing in order to accommodate the 2,4-D and 2-CEPA anions which are larger in size than nitrate. FTIR spectrum of both prepared ZANDI and ZANE nanocomposites resembled a mixture of each parent material, ZALs and guest anions of 2,4-D and 2-CEPA, indicating the presence of both in the resulting materials. Taken together the X-ray diffraction and FTIR analyses, successful formation of ZANDI and ZANE were further confirmed. Further physico-chemical characterisations of the resulting materials including thermal analysis, elemental analysis, surface area and porosity and surface morphology, were also carried out. The controlled release study of 2,4-D and 2-CEPA were done in aqueous media of sodium chloride, sodium carbonate and sodium phosphate at 0.05 M. Release of 2,4-D and 2-CEPA were also done in water as control. It was found that 2,4-D and 2-CEPA were rapidly released in sodium carbonate and sodium phosphate, respectively. However, the release percentage of 2,4-D was found to be the highest in carbonate at 99 % and for 2-CEPA in sodium phosphate at 98 % . The kinetic model of pseudo-second order fits well with all of the release profile with r2 > 0.9. CNT from the calcined CoNiAl-LDH was produced with high yield when compared to calcined FeCoNiAl-LDH and FeNiAl-LDH. However, CNTs from calcined FeCoNiAl-LDH was found in abundance after the purification took place. CNTs synthesised by using the metal foils afforded much smaller diameter and better surface properties which could be due to the well dispersed highly pure metal.